THE ROLE AND IMPORTANCE OF THE CORPORATE MANAGEMENT SYSTEM OF THE MODERNIZATION OF THE JOINT-STOCK COMPANY IN THE MODERNIZATION AND DIVERSIFICATION OF THE ECONOMY - Uktamjonova, Z.A.; Omonov, A.D.; Tursunaliyev, M.N (Educational Research in Universal Sciences, 2023)
A joint-stock company is the principle of contribution of earning income in a mutual or organized state on the basis of partnership. It also differs from a partnership enterprise in that it issues shares with a nominal amount for circulation and sells them on this basis. This article applies the methods of ensuring the organization of the corporate management system and maximum modernization in the diversification of the economy in the joint-stock company.